Metric based software project performance monitoring model - Doraisamy, M. (Penerbit UTM Press, 2016)
Successful implementation of software projects development is entirely depending upon successful monitoring and control mechanism. Software metrics can deliver the necessary information for monitoring and control the software projects development for its enhancement. However, the current software metrics does not widely address the performance criteria and related metrics for software project management. Largely, metrics are identified in the perspectives of software development only. Hence, the aim of this study is to formulate a Metric based Software Project Performance Monitoring Model which consists of performance criteria and metrics that involves in a software projects development. This model formulation is consists of five processes: metrics integration, metrics validation, metrics description, metrics categorization and metrics threshold. The proposed model is a novel approach and adds significant of knowledge to the software engineering domain especially on software project monitoring and software measurement domain. Generally, this model will be a guideline for software project managers to monitor and control software projects particularly in public sector software projects. In order to demonstrate the applicability of this model, case study was conducted at various departments at Malaysian Public Sector. The results show that the proposed model is very useful for the project managers in monitoring and control software projects.